Effect of Integrated Application of Poultry Manure and Chemical NP Fertilizers on Growth, Yield and Yield Components of Highland Maize Variety on Vertisol at Ambo University on Station, Ethiopia - Kusse, Tulu; Balemi, Tesfaye; Abera, Tolera (International Journal of Sustainable Agricultural Research, 2019)
A decline in soil nutrient and organic matter content as a consequence of removal of crop residues from crop fields, repeated suboptimal fertilization resulting in periodic nutrient mining, is a major constraint to increasing maize productivity in a sustainable manner in tropical soils. A field experiment was conducted at Ambo University research farm, Ethiopia with the objectives to investigate: the effect of combining different levels of poultry manure (PM) and NP chemical fertilizer rates on growth, yield and yield components of maize (Zea mays L.). The experiment consisted of eight treatments: control, 15 t ha-1 PM alone, 30 t ha-1 PM alone, 15 t ha-1 PM + 25% rec. NP, 15 t ha-1 PM + 50% rec. NP, 30 t ha-1 PM + 25% rec.NP, 30 t ha-1 PM + 50% rec.NP and 100% recommended dose of NP fertilizer rates, which were laid out in randomized complete block design (RCBD) with three replications. Results showed that plant height, number of leaves per plant, leaf area, leaf area index, number of cobs per plant, cob girth, cob length, number of grains per cob, 1000-grain weight, biomass yield, harvest index and grain yield were significantly higher for the treatment in which 30 t ha-1 PM plus 50% recommended NP fertilizer was applied compared to both the absolute and standard controls. The highest maize grain yield (132.7q ha-1) was recorded for the treatment in which 30 t ha-1 PM along with 50% recommended NP fertilizer was applied. The lowest values of growth, yield and yield components parameters were recorded for the negative control where no PM and chemical NP fertilizer were applied. Results of the correlation analysis revealed the presence of significant positive relationship between grain yields and all growth and yield component parameters. Integrating poultry manure with chemical fertilizers can considerable reduce the quantity of the later required for optimum maize production.